“Just Ask Me”: The Importance of Respectful Relationships Within Schools - Brownlow, Charlotte; Lawson, Wenn; Pillay, Yosheen; Mahony, Joanne; Abawi, Ding (Frontiers in Psychology, 2021)
An inclusive approach to education requires schools and educators to address the support needs and individual predispositions of all students. Our research highlights the crucial importance of effective and respectful communication with autistic students to facilitate their successful participation in schools. This paper explores the experiences of 24 autistic individuals through synchronous interviews and written responses. The research team comprised both autistic and allistic (non-autistic) researchers, who worked together to design the overall project, collect interview data, and analyse the data. Relationships were frequently discussed by participants and the importance of positive relationships was positioned as key to successful participation within educational contexts. Particularly damaging were assumptions made by teachers concerning individual ability based on labels given. Participants recalled ongoing challenges with resisting stereotypes and managing stigma, while trying to craft a positive autistic identity and advocate for rightful supports for their education. At the core of these negotiations were positive relationships, and teachers who asked participants what their needs were, and then listened and proactively responded to their answers.